Endothelial cell supplementation promotes xenograft revascularization during short-term ovarian tissue transplantation - Spazzapan, Mariagiulia; Pegoraro, Silvia; Vuerich, Roman; Zito, Gabriella; Balduit, Andrea; Longo, Elena; Pascolo, Lorella; Toffoli, Miriam; Meshini, Giorgia; Mangogna, Alessandro; Ros, Gloria; Buonomo, Francesca; et al. (Bioactive materials, 2025)
The ischemic/hypoxic window after Ovarian Tissue Transplantation (OTT) can be responsible for the loss of more than 60 % of follicles. The implantation of the tissue supplemented with endothelial cells (ECs) inside dermal substitutes represents a promising strategy for improving graft revascularization. Ovarian biopsies were partly cryopreserved and partly digested to isolate ovarian ECs (OVECs). Four dermal substitutes (Integra®, made of bovine collagen enriched with chondroitin 6-sulfate; PELNAC®, composed of porcine collagen; Myriad Matrix®, derived from decellularized ovine forestomach; and NovoSorb® BMT, a foam of polyurethane) were compared for their angiogenic bioactive properties. OVECs cultured onto the scaffolds upregulated the expression of angiogenic factors, supporting their use in boosting revascularization. Adhesion and proliferation assays suggested that the most suitable scaffold was the bovine collagen one, which was chosen for further in vivo experiments. Cryopreserved tissue was transplanted onto the 3D scaffold in immunodeficient mice with or without cell supplementation, and after 14 days, it was analyzed by immunofluorescence (IF) and X-ray phase contrast microtomography. The revascularization area of OVECs-supplemented tissue was doubled (7.14 %) compared to the scaffold transplanted alone (3.67 %). Furthermore, tissue viability, evaluated by nuclear counting, was significantly higher (mean of 169.6 nuclei/field) in the tissue grafted with OVECs than in the tissue grafted alone (mean of 87.2 nuclei/field). Overall, our findings suggest that the OVECs-supplementation shortens the ischemic interval and may significantly improve fertility preservation procedures. [Display omitted] •ECs combined with dermal substitutes represent a promising strategy for OTT.•Supplementation with ECs in ovary transplantation enhanced tissue revascularization.•IF confocal analysis detected the formation of mature mosaic-vessels (ms-hu).•X-ray phase-contrast microtomography showed vessel-like structures inside tissue.•Iodine staining highlighted the migration of cells from scaffold towards the tissue.